HISTORY OF SOCIOLINGUISTICS AND ITS FUNCTION IN MODERN LINGUISTICS - Sayidov Shukrullo Khaliljonovich; Jumabaeva Sevinch Kopjursin qizi (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
In global linguistics, applied linguistics deals with the practical realization of linguistic potential and the effective use of language. It addresses pressing issues within various modern fields such as sociolinguistics, ethnolinguistics, psycholinguistics, pragmalinguistics, cognitive linguistics, linguistic cultural studies, neurolinguistics, computational linguistics, and corpus linguistics. The fact that contemporary linguistic research has already established new directions that examine the interrelation of language with practice, speech, society, culture, national thinking, and even artificial intelligence sets new tasks for our field. Such factors indicate the emergence of diverse new goals and objectives within the realm of sociolinguistics. The development of this discipline, which emerged at the intersection of sociology and linguistics, naturally depends on the extent to which these fields have been studied. In other words, it is only natural that social events and phenomena occurring in everyday life are reflected in language to some degree.